INFLUENCE OF FOLIAR APPLICATION OF ZINC ON SEED YIELD AND ITS COMPONENTS IN SOME ALFALFA VARIETIES - Khrbeet, H.K. (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2018)
This study was carried out at the experimental farm College of Agriculture; Abu-Ghraib, Baghdad, Iraq during from end of march 2014 to mid of August 2015. The main objective was to find out the effect of zinc concentration (0, 30, 60 and 90) mg.L-1 on seed yield and its components of four alfalfa varieties (Local, Hamaddan, Vernal and Lodi). Layout of the experiment was R.C.B.D arranged within split –plots with three replications. Zinc concentration were used as main plot, while varieties were used as sub-plot. Results, showed that foliar application of zinc at concentration more than 30 mg.L-1 (60 and 90 mg.L-1) resulted in a significant increment in the No. of ovules floret-1, No. of seed pod-1, No. of stems m-2, No. of racemes stem-1, No. of pods raceme-1 and seed yield. Kg.ha-1 in contrast, percent of ovules abortion was significantly reduced, while 1000 seed weight was not significantly influenced by Zinc concentrations. Highest seed yield (535.0 Kg.ha-1) was obtained when Zinc added at level 60 mg.L-1. Local var. produces higher No. of ovules floret-1, No. of seed pod-1, No. of stem.m-2, and No. of racemes stem-1 and it was significantly different than other varieties except var. Hamddan. Increasing of all these traits resulted in increasing of seed yield in local var. (532.5 Kg.ha-1. There was high positive correlation between seed yield and each of seed set, No. of stem. m-2 and No. of pods raceme-1 (+ 0.75**, +0.66** and 0.78**) respectively. This result may be indicating that these traits could be used as good selection criteria for breeding and improving seed yield in alfalfa varieties. highest seed yield (620.2 Kg.ha-1) can be obtained by seeding local variety. and spray the stands with Zinc at concentration 60 mg.L-1.